Response of Extraintestinal Pathogenic Escherichia coli to Human Serum Reveals a Protective Role for Rcs-Regulated Exopolysaccharide Colanic Acid. - SMITH, STEPHEN; MORAN, GARY; ROGERS, THOMAS (My University, 2014)
Extraintestinal Escherichia coli (ExPEC) organisms are the leading cause of Gram-negative bacterial bloodstream infections. These bacteria adapt to survival in the bloodstream through expression of factors involved in scavenging of nutrients and resisting the killing activity of serum. In this study, the transcriptional response of a prototypic ExPEC strain (CFT073) to human serum was investigated. Resistance of CFT073 to the bactericidal properties of serum involved increased expression of envelope stress regulators, including CpxR, σE, and RcsB. Many of the upregulated genes induced by active serum were regulated by the Rcs two-component system. This system is triggered by envelope stress such as changes to cell wall integrity. RcsB-mediated serum resistance was conferred through induction of the exopolysaccharide colanic acid. Production of this exopolysaccharide may be protective while cell wall damage caused by serum components is repaired.
PUBLISHED
Keywords: Extraintestinal Escherichia coli (ExPEC); Immunology, Inflammation & Infection